A two centre study of the dose-response relation for transscleral diode laser cyclophotocoagulation in refractory glaucoma. Issue 10 (23rd September 2003) - Murphy, C C; Burnett, C A M; Spry, P G D; Broadway, D C; Diamond, J P
Abstract : Background/aims: Transscleral diode laser cyclophotocoagulation ("cyclodiode") is widely used to treat refractory glaucoma. The main aims of this study were to investigate the dose-response relation of cyclodiode and to evaluate possible predictive factors that would help establish optimum treatment parameters. Methods: A retrospective analysis of the case notes of 263 eyes of 238 consecutive patients who underwent transscleral diode laser cyclophotocoagulation at two centres was undertaken. Results: Mean intraocular pressure (IOP) decreased significantly from 40.7 mm Hg (SD 13.7) before cyclodiode therapy to 17.7 mm Hg (SD 10.9) post-treatment, a reduction of 52.6% (p = 0.0001). Following cyclodiode, 89% of patients achieved an IOP of less than 22 mm Hg or a greater than 30% drop in IOP. Hypotony occurred in 9.5% of patients, 76% of whom had neovascular glaucoma. A linear dose relation response was found for the 122 eyes with neovascular glaucoma (p = 0.001) but not for the group as a whole. Treatment failure was associated with male sex (multivariate regression analysis, p = 0.008) and low mean energy per treatment session (univariate analysis alone, p = 0.016). High pretreatment IOP (p = 0.031) and high mean energy per treatment episode (p = 0.001) appeared to be associated with the occurrence of hypotony, although multivariate analysis did not support this finding. Conclusion: Cyclodiode therapy is highly effective but there is a significant risk of hypotony, which may be reduced by applying lower energy in cases of very high pretreatment IOP and in neovascular glaucoma. The dose-response association remains unpredictable, although a linear relation was found for neovascular glaucoma.